MENUMBUHKAN CINTA BUDAYA MELALUI PENGENALAN MOTIF BATIK TRADISIONAL DAN PAHLAWAN NASIONAL PADA ANAK-ANAK PMI DI MALAYSIA - Hasanah, Aldhania Uswatun; Azizah, Siti Nur; Wulandari, Yuli Arisa; Oktyaramadhan, Afifia Puspa; Kusumah, Meutya Qiran Noor Azizah Putri; Sitanggang, Rhebecca Paulene Lay; Puri, Annisa Aulia; Purnomo, Ryan (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
This community service activity aims to foster a sense of love for culture and nationalism among Indonesian Migrant Students (PMI) in Malaysia through the introduction of traditional batik motifs and national hero figures. This program combines two main methods, namely game-based teaching media and batik practice. Game-based teaching media involves the use of interactive quizzes and creative competitions that present the values of the struggle of national heroes in a fun and interesting way. In addition, batik practice is carried out by providing direct demonstrations of batik making and opportunities for students to try making their own batik motifs. This activity is designed so that children can see and feel the process of making batik, as well as understand the cultural values contained in it. The results of this activity show that PMI children not only succeeded in understanding the history of the nation's struggle and getting to know the hero figures, but also felt proud of Indonesia's cultural heritage. This program has a positive impact in strengthening students' sense of nationality and cultural identity, even though they live far from their homeland. In addition, a creative and interactive learning approach through games and direct practice has proven effective in improving students' understanding of the material and fostering a spirit to preserve Indonesian culture. It is hoped that this program can be continued with further development so that it can reach more PMI children abroad.